Oligophenyls with Multiple Disulfide Bridges as Higher Homologues of Dibenzo[c,e][1,2]dithiin: Synthesis and Application in Lithium-Ion Batteries - Sonnenschein, Christoph; Ender, Christopher P.; Wang, Faxing; Schollmeyer, Dieter; Feng, Xinliang; Narita, Akimitsu; Muellen, Klaus (Chemistry - A European Journal, 2020)
Higher homologues of dibenzo[c,e][1,2]dithiin were synthesized from oligophenyls bearing multiple methylthio groups. Single-crystal X-ray analyses revealed their nonplanar structures and helical enantiomers of higher meta-congener 6. Such dibenzo[1,2]dithiin homologues are demonstrated to be applicable to lithium-ion batteries as cathode, displaying a high capacity of 118 mAh g−1 at a current density of 50 mA g−1.
CRIS-Team Scopus Importer:2023-03-20
Keywords: dibenzo[1; 2]dithiin; lithium-ion batteries; oligophenyls; polycycles; sulfur heterocycles